The Search for the Gene - Wallace, Bruce, 1920-2015 (Book collections on Project MUSE., 1992)
From Gregor Mendel's experiments on garden peas to the mammoth Human Genome Project of today-how did we get where we are in the science of genetics? In this intriguing book, Bruce Wallace examines the concept of the gene and recounts the history of genetic research, providing a concise transition from genetics to modern molecular biology.